Theory of Management and Educational Leadership: Conceptual Analysis and Its Application in Educational Institutions - Idris, Ahmad; Firdaus, Arif Fakih; Nuroniyah, Mila; Syarifudin, Encep; Bachtiar, Machdum (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2025)
Education management is an important aspect in the management of educational institutions. With the various challenges faced, understanding management theories is crucial. This article will analyze some relevant theories of education management, such as classical theory, systems theory, and contingency theory, as well as their application in schools. This article discusses various theories of education management and how they are applied in the context of schools. Through conceptual analysis, this research aims to understand the relationship between management theory and practice in the field, as well as provide recommendations to improve the effectiveness of education management in schools. This research aims to examine how these theories are applied in the context of schools and how effective implementation can support the improvement of the quality of education. The results of the study show that the implementation of proper management in schools plays a major role in improving the efficiency, effectiveness, and sustainability of the management of educational institutions.